Defunding Hate: PayPal’s Regulation of Hate Groups - Tusikov, Natasha (Surveillance & society, 2019)
The riot by white supremacists in Charlottesville, Virginia, in August 2017, generated a public debate about the role of platforms in policing users involved in violent hate speech. PayPal’s efforts on this issue, in removing services from some designated hate groups while continuing to serve others, highlights the challenges payment platforms face when they act, whether formally or informally, as regulators. This article examines PayPal’s policies and enforcement efforts, both proactive and reactive, in removing its services from hate groups in the United States. It pays particular attention to the surveillance and screening practices that PayPal employs to proactively detect users who violate its policies. The article argues that public calls for PayPal to identify and remove its services from hate groups raise critical questions about ceding broad regulatory authority to platforms and reveal the serious challenges of relying upon commercial enterprises to address complex social problems.